Clinical manifestations of Brucellosis in domestic animals and humans - Megid, Jane [UNESP]; Mathias, Luis Antonio [UNESP]; Robles, Carlos (Bentham Science Publishers, 2010)
Brucellosis in domestic animals is a chronic disease that is characterized mainly by reproductive signs in cattle, buffaloes, pigs, sheep, goats and dogs. In females the disease is characterized by abortion, placenta retention, vaginal secretions, low fertility rate and also embryonic and neonatal death. In males, regular findings include epididymitis, orchitis, uni - or bilateral testicular atrophy, sperm abnormalities and infertility. Lymphadenopathy, hepatopathy, splenomegaly, uveitis and discospondylitis may also be observed in dogs. In horses, the typical clinical sign is characterized by a granulomatous supraspinous or supra-atlantal bursa lesion. Infected animals can also be asymptomatic. Infected symptomatic or asymptomatic animals represent an important source of infection to other animals and humans. Brucellosis in humans can cause undulant fever, malaise, insomnia, anorexia, headache, arthralgia, constipation, sexual impotence, nervousness and depression. For all species the presentation of clinical signs are only suggestive of disease infection and thus must be differentiated from other diseases.
Keywords: Brucellosis; Clinical signs; Review; Cattle; Buffaloes; Dogs; Sheep; Goats; Human